(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
The theme of existential courage is one that has always attracted my attention. In this article, I will discuss existential courage and its relationship to a few other existential givens, such as freedom, authenticity, meaning and finitude in order to highlight its importance. It will also explore the relationship of courage to will and love, and the possible connection of childhood experiences for its development.